Strategic pre-clinical development of Riminophenazines as resistance circumventing anticancer agents - Greeff, O.B.W. (Oppel Bernhardt Wilhelm), 1948- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.